A Transdermal Measurement Platform Based on Microfluidics - Wen-Ying Huang; Jung-Ping Huang; Chia-Ching Lin; Yung-Sheng Lin (Journal of Chemistry, 2017)
The Franz diffusion cell is one of the most widely used devices to evaluate transdermal drug delivery. However, this static and nonflowing system has some limitations, such as a relatively large solution volume and skin area and the development of gas bubbles during sampling. To overcome these disadvantages, this study provides a proof of concept for miniaturizing models of transdermal delivery by using a microfluidic chip combined with a diffusion cell. The proposed diffusion microchip system requires only 80 μL of sample solution and provides flow circulation. Two model compounds, Coomassie Brilliant Blue G-250 and potassium ferricyanide, were successfully tested for transdermal delivery experiments. The diffusion rate is high for a high sample concentration or a large membrane pore size. The developed diffusion microchip system, which is feasible, can be applied for transdermal measurement in the future.